COMBINING ABILITY ESTIMATES AND GENE EFFECTS FOR GRAIN YIELD AND YIELD COMPONENTS IN MAIZE (ZEA MAYS L.) - Yasser H. S. AL-Aaty (European Journal of Agricultural and Rural Education, 2021)
Nine inbred lines of maize were used in this study, which entered in crosses according to the method of factorial mating system, where the lines DK, OH40 and ZP-607 used as females and lines ZM47R, G105, ZM51, ZM49R, Inbreed2 and G54 used as male parents. The parents and the first generations of their single crosses planted through autumn season of 2013 at Al-Hawija, Kirkuk Province using randomized complete block design with three replications, then data recorded for characters, plant height, main ear height, number of ears per plant, ear length, ear diameter, number of rows per ear, number of grains per row, number of grains per ear, 300 grain weight and grain yield per plant. The results showed that there are highly significant differences between genotypes (parents and hybrids) for all characters. The two lines OH40 and G54 given desirable significant effects of general combining ability for the largest number of characters. The hybrids showed variation in their effects of specific combining ability for different characters, and the hybrids (OH40 x ZM51), (ZP-607 x G549) and (DK x G105) characterized by desirable specific combining ability for the largest number of characters including grain yield per plant. Additive genetic variance appeared largest in its value than dominance one for plant height, main ear height, ear length, ear diameter, number of grains per row and number of grains per ear, and vice versa for the rest of characters. Average degree of dominance was less than one for main ear height and number of grains per ear, indication of a partial dominance, and was more than one for the rest of the characters indicating over dominance. The broad sense heritability ranged between 57.834% for number of grains per ear and 95.565% for main ear height, and in narrow sense between 21.053% for number of ears per plant and 67.218% for main ear height.